Microbial Sulfur Metabolism 2008
DOI: 10.1007/978-3-540-72682-1_12
|View full text |Cite
|
Sign up to set email alerts
|

Redox Control of Chemotrophic Sulfur Oxidation of Paracoccus pantotrophus

Abstract: The reaction cycle of the reconstituted Sox enzyme system of Paracoccus pantotrophus requires the periplasmic proteins SoxYZ, SoxXA, SoxB, and SoxCD. The heme enzyme SoxXA covalently binds the sulfur substrate to the thiol of the single cysteine residue of SoxY located at its carboxy-terminal end. Bound sulfur is then oxidized to sulfate by a series of reactions. These involve sulfur dehydrogenase SoxCD which oxidizes the protein-bound sulfane sulfur to sulfone in a unique six-electron transfer. Bound sulfone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
(38 reference statements)
0
31
0
Order By: Relevance
“…Homogeneous SoxF has a sulfide dehydrogenase activity in vitro [17]. This activity, however, is not considered to be of relevance in vivo since P. pantotrophus harbors three different sulfide-oxidizing activities [18] and SoxF affects the thiosulfate metabolism [16]. Moreover, SoxF does not function in sulfur oxidation in vitro in the Sox enzyme system as reconstituted from homogeneous active Sox proteins.…”
Section: Cys110mentioning
confidence: 99%
“…Homogeneous SoxF has a sulfide dehydrogenase activity in vitro [17]. This activity, however, is not considered to be of relevance in vivo since P. pantotrophus harbors three different sulfide-oxidizing activities [18] and SoxF affects the thiosulfate metabolism [16]. Moreover, SoxF does not function in sulfur oxidation in vitro in the Sox enzyme system as reconstituted from homogeneous active Sox proteins.…”
Section: Cys110mentioning
confidence: 99%
“…A survey of the B. japonicum USDA110 genome revealed multiple homologues of sox genes; however, it was not clear if these homologues were functional for the oxidation of inorganic sulfur compounds and chemolithotrophic growth in this bacterium (7). The sox gene cluster in P. pantotrophus GB17 comprises at least 15 genes, soxTRSVWXYZABCDEFGH, which are responsible for thiosulfate oxidation and chemolithotrophic growth (9).…”
mentioning
confidence: 99%
“…Thiosulfate is one of the most-abundant forms of reduced sulfur in nature, and the ability to oxidize this compound is distributed over many microorganisms across different phyla (6,7,14,19,21,43). It sometimes occurs that some members within a phylum can utilize thiosulfate while others cannot.…”
mentioning
confidence: 99%
“…From the direct sequencing of the sox genes, as well as from the results of current whole-genome-sequencing projects, genes predicted to be involved in inorganic sulfur metabolism have been identified in a variety of microorganisms, including many of the genes encoding Sox proteins (soxA, soxB, soxF, soxX, soxY, and soxW) that occur in a cluster as in P. pantotrophus (19,21,22). In the green sulfur bacterium C. limicola f. thiosulfatophilum, Verté et al (60) reported that sox genes occur in a similar cluster.…”
mentioning
confidence: 99%